Relation between mitral valve closure and early systolic function of the left ventricle. - Smalcelj, A (1985)
In order to investigate relations between mitral valve closure and mechanical events at the onset of left ventricular systole, simultaneous M mode echocardiograms and phonocardiograms were recorded with the apexcardiogram and its first differential (dA/dt) in 25 normal subjects and 88 patients with heart disease. The timing of mitral and aortic valve closure and the onset and peak rate of rise of the apexcardiogram with respect to the Q wave of the electrocardiogram were measured. There was considerable variation in the intervals from Q to mitral valve closure (Q-MVC) and from Q to peak dA/dt and in the isovolumic contraction time between normal subjects. There was no consistent abnormality of these intervals in patients with coronary artery or valvar disease, and no relation between the interval from Q to mitral valve closure and end diastolic pressure. When the timing of the first heart sound and peak dA/dt were considered together, however, clear abnormalities became apparent. In normal subjects, the intervals Q-MVC and Q to peak dA/dt were significantly correlated. In coronary artery disease, the expected relation between Q-MVC and Q to peak dA/dt was found only when end diastolic pressure was normal and was lost when end diastolic pressure was raised. Mitral stenosis was associated with delayed mitral closure in a few cases only, but in chronic aortic regurgitation closure was consistently early with respect to the apexcardiogram. In patients with atrial fibrillation and a normal mitral valve the timing of mitral valve closure with respect to the apexcardiogram was normal, which is inconsistent with an atrial contribution to the timing of mitral valve closure. Thus when considered in isolation the timing of mitral valve closure and the duration of isovolumic contraction time gave little information about cardiac function. Nevertheless, a predictable relation exists between mitral valve closure and the onset of left ventricular mechanical systole in normal subjects, which can be used to identify characteristic alterations in patients with heart disease.